Finding Out the Root of Congestion Problems in Malang City and the Best Solution with Public Policy Analysis - Alfareza Firdaus; Dzakiyah Adalatul Hikmah; Edmund Patrisius Purna (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Traffic congestion has a significant negative impact on regional economic activities and decreases community productivity.  The purpose of this study is to analyze the sources of congestion problems in Malang City and the best way to solve them with a high level of effectiveness. The method used is qualitative with secondary data study. The researcher used a classification-based analysis approach to address the congestion problem with a multidisciplinary approach and explore the root of the congestion problem in Malang City. The first step involves logical division to classify the problem situation into several components. Second, logical classification refers to the act of combining different circumstances, things, or individuals into larger groups or classes. The results showed that the source of the problem was found in the high volume of vehicles and disorderly parking due to the growing accumulative population mobility. As a result, the capacity of Malang City is not able to accommodate this. Recommendations from alternative options resulting from the satisficing method analysis were carried out. In the end, the option to reorganize the road space is the option that is considered to meet all the criteria.